Academic visit to the School of Pharmaceutical Sciences (PPSF), Universiti Sains Malaysia (USM) / Sofia Umaira Ismail, Muhammad ‘Izzuddin Zamery and Dr. Gurmeet Kaur Surindar Singh - Ismail, Sofia Umaira; Zamery, Muhammad ‘Izzuddin; Surindar Singh, Gurmeet Kaur (Faculty of Pharmacy, 2023)
In the wake of the COVID-19 pandemic, the world has faced numerous challenges, and the education sector has not been spared. Nevertheless, the Faculty of Pharmacy, UiTM Puncak Alam recently had its first in-person visit to another institution since the pandemic began to subside. The visit was held on March 16, 2023, at the School of Pharmaceutical Sciences (PPSF), Universiti Sains Malaysia (USM).